The Effect of Discovery Learning on Student Learning Outcomes: Elasticity and Static Fluid Contexts - Putri Dwi Sundari; Zulfadhlil Haqi; Hufri Hufri; Hidayati Hidayati (Postgraduate, University of Mataram, 2024)
Physics learning at school still shows the implementation of the learning model teacher's use is still learning with a teacher-centred teaching and learning process that creating low student learning outcomes. Therefore, a study was conducted by employing the discovery learning model to increase student learning outcomes. The type of research conducted was a quasi-experiment with the research design RandomisedPossttest Only Control Group Design. With the same number of sample class members, namely 36 students. The research data includes student physics learning outcomes on cognitive aspects. Data analysis techniques employed are normality test, homogeneity and hypothesis testing at the real level of 0.05. Based on data analysis, average physics learning outcomes of students in the knowledge aspect of the experimental class is 82 higher than the control class which is 76. Hypothesis testing of the posttest conducted tcount<ttable where 2.52 > 1.66 H0 is rejected and H1 is accepted, it can be concluded in the study that the usage of the discovery learning model has a significan effect on the physics students' learning outcomes a real level of 0.05.